Forme abitative rurali nel territorio fra l’Alma e l’Ombrone*: due casi esemplari fra l’arcaismo e la prima età imperiale - Paribeni , Emanuela; Rafanelli, Simona (O T I V M, 2018)
If compared to the Etruscan Farm (6th - 5th cent. BC) along the river Alma, which is an emblematic case of political and cultural dominance of Vetulonia throughout the entire existence of a settlement, the case of the Villa of Nomadelfia (1st cent. BC - mid-2nd cent. AD) is very unusual: built in a ’liminare’ territory, belonging to the Etruscan Vetulonia at first, and then to the contiguous polis of Rusellae (here the reason of the title). In this preliminary study, the examination of these two cases has brought out interesting common aspects, despite the different chronology: the formal contamination between the city and country residences; the development of variants compared to the ’canonical’ planimetric model; the transposing of basic traditional elements of the house into the modern type of domestic architecture.